The effects of a four week jump-training program on frontal plane projection angle in female gymnasts - Colclough, A.; Munro, A. G.; Herrington, L. C.; McMahon, J. J.; Comfort, P. (Physical Therapy in Sport, 2018)
Objectives: To investigate the effects of a four week jump training program on frontal plane projection angle (FPPA) in young female gymnasts. Design: Intervention study, consisting of a four week jump training program performed for 15 min as part of a warm-up, three days per week for four weeks. Setting: Gymnastics training center. Participants: Fourteen youth female gymnasts (age: 13.5 ± 2.14 years, height: 1.54 ± 0.11 m, body mass: 46.23 ± 7.68 kg). Main outcome measures: Change in FPPA during a 30 cm drop landing and tuck back somersault. Results: Large and significant decreases (p < 0.001) in FPPA of 6.8° (39%) and 8.4° (37%) during the drop landing and tuck back somersault, respectively. Conclusion: The jump training program was successful in improving FPPA in female gymnasts and is advised to be implemented into the warm-ups and training programs of competitive female gymnasts to improve FPPA and therefore reduce the risk factors associated with knee injuries.